Perception attitude and exercise compliance among menopausal females - Parle, Jyoti; Parmar, Reema; Khan, Lubna (International Journal Of Community Medicine And Public Health, 2021)
Background: Menopause is perhaps the most striking event occurring during the middle age in women and represents the end of woman’s reproductive life. With the general increase in life expectancy, many women are likely to live for more than 20 years after menopause, spending about one quarter of their lives or more in a state of oestrogen deficiency. Owing to lack of oestrogen woman may experience decrease physical and mental wellbeing that’s why postmenopausal woman can be considered a risk population. There is a lack of data to find the compliance and attitude towards exercise among menopausal females in India. Methods: A questionnaire-based survey was conducted among sample size of 150 menopausal females. Self-made questionnaire was the outcome measure. Results: 21% consider menopause is associated with changes in the body.1 % perceived all the symptoms to be associated with menopause.30% perceived that none are associated with menopause. Perception was seen to be positive overall.36% of uneducated females do not consider exercise at all important.51% of educated females consider it important. Only 61% exercise on regular basis. Conclusions: Most females perceive menopause as a positive life event. Exercise was considered somewhat important by menopausal females; however exercise compliance was poor.